Evaluasi dan Pengembangan Media Pembelajaran Website Algoritma: Study Kasus di Universitas Abdurrab Pekanbaru - Cahyono, Kori (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2015)
This study aimed to evaluate the instructional media used in lecture algorithms and data structures at the University Abdurrab (Univrab) Pekanbaru. In particular, this study aims to obtain information on the learning process using the web-based media on learning algorithms and analysis of instructional media development needs. The method of research is the study of evaluation and analysis of the development needs of instructional media. Respondents were students of 3rd semester academic year 2015 took the course of the algorithm. Data collection was used documentation techniques methods and media assessment questionnaire used as the reference in analyzing the needs and revise media used in learning. Data were analyzed using quantitative and qualitative descriptive analysis, to describe the process of learning and development needs analysis media. The results showed that the teaching media courses based algorithms website (e-learning) are used effectively can make it easier for students to understand the material algorithms. Needs development of instructional media is more focused on the addition of interactive animation content to provide ease of learning, understanding the concept is too abstract and development policy learning blended learning models